Financial Performance of the Adventist Book Centers in the Southern Asia-Pacific Region: A Comparative Analysis - Lule, Benny (JBE (Journal of Business and Economics), 2008)
This study is a quantitative research. It aims to assess and compare the financial performance of seventeen (17) ABCs in the Southern Asia-Pacific Region. Descriptive statistics and Mann-Whitney U test were used to address the main objective of the study. Eleven years, from 1993 to 2003, the ABCs’ financial data and other related data have been taken to be used in this study. Empirical findings of the study show that the ABCs in Non-Indonesia (Group 2) have better financial performance compared to the ABCs in Indonesia (Group 1). Specifically, the statistical test reveals that there is significant difference in financial performance between Group 1 and 2.